Respuesta :
Answer:
x = 6 , y= -2
Step-by-step explanation:
=1 ( 2x + 3y =6)
2( x+y=4)
2x+3y =6 (1)
2x+2y = 8 (2)
by eq 1 and 2 using elimination method
y = -2
putting y in eq 2
2x + 2(-2)=8
2x -4 =8
2x =8+4
2x=12
x= 6
Answer:
x = 6 , y = -2
Step-by-step explanation:
2 x + 3 y = 6 (Equation 1)
x + y = 4 (Equation 2)
Solving by substitution :
(Equation 2) ⇒ y = 4 - x
Substitute y by 4 - x in (equation 1) :
2 x + 3 (4 - x) = 6
Then
2 x + 12 - 3x = 6
Then
12 - x = 6
Then
12 - 6 = x
Then
x = 6
We obtain :
y = 4 - x and x = 6
Then
y = 4 - 6
= -2